"Mental Readiness" and Gatekeeping in Trans Healthcare. (November 2022) - Verbeek, Wesley; Baici, Wayne; MacKinnon, Kinnon R.; Zaheer, Juveria; Lam, June Sing Hong
Gatekeeping refers to clinicians' strict application of eligibility criteria to determine a trans patient's "fitness" to engage in medical transition, resulting in significant barriers to gender-affirming care. Gatekeeping often uses "mental readiness" as a prerequisite to medical transition, which contributes to patient distress and systemic discrimination. Changing international trans health guidelines (the new World Professional Association for Transgender Health Standards of Care version 8) recommends clinicians shift from a gatekeeping model towards an informed consent model, which improves access to care. This commentary offers recommendations on how clinicians can reconsider existing "mental readiness" frameworks around medical transition to facilitate improved access to care.